Review paperSelected skin diseases caused by sunlight exposure - Kujawska-Dębiec, Karolina; Broniarczyk-Dyła, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
The sun plays an important role in our life; it is essential for our mind and body. The most important effects of sunlight on the human body are: the synthesis of melanin and vitamin D, alterations in the immune system and carcinogenesis. The intensity of sunlight increases in the springtime, which initiates several dermatoses induced by UV irradiation. Sun rays may cause a broad group of photodermatoses, e.g.: polymorphic light eruption, solar urticaria, hydroa vacciniforme, actinic prurigo, phototoxic and photoallergic reactions. The paper presents selected skin diseases provoked by UV and their treatment.